Inventarisasi Awal Liken Langka, Sensitif dan Toleran sebagai Bioindikator Polutan di Kabupaten Belitung Barat : Preliminary Inventory of Rare, Sensitive and Tolerant Lichens as Bioindicators of Pollutants in West Belitung Regency - I Sudirman, Lisdar; Fitri, Devi Risvia; Purnama, Meggi Rhomadona (Jurnal Sumberdaya Hayati, 2024)
The existence and population conditions of the rare, sensitive or tolerant lichens of Lobaria, Coccocarpia, Coenogonium, Dictyonema, Pseudocyphellaria, Sticta, Usnea, Leptogium, and Parmotrema tinctorum are not yet known in West Belitung Regency, so this research needs to be carried out. The method used in this research was exploratory descriptive with survey techniques and purposive sampling. The number of target lichen thallus was calculated from the entire area of the tree trunk with a height of 0-1.5 m. The lichens found in the Gunung Tajam area were Coccocarpia sp. with the highest number of thallus and the highest frequency of thallus (0.8%), followed by Coenogonium sp., Leptogium sp., and Usnea sp. with the same frequency of thallus (0.4%) while in the Batu Mentas area lichens were not found as the research target, but was dominated by fruticose lichen. Parmotrema tinctorum, the tolerant lichen, was not found at either location. The presence of sensitive lichens and the absence of tolerant lichens does not indicate that the locations have good air quality. It is recommended that the lichen population, especially P. tinctorum, be studied further so that air quality can be easily confirmed through the diversity and population of the lichens.